The Influence of Risk Perception and Financial Literacy on Interest in Using Online Loans - Nur Amalia, Saebah Nur Amalia; Sari, Widya (Jurnal Accounting Information System (AIMS), 2026)
Based on observations and interviews, the background to this research is the fluctuation in the number of online loan users in West Java, a case study of the Cimekar Village community in Bandung Regency. This study aims to determine the influence of risk perception and financial literacy on interest in using online loans, both simultaneously and partially. The research subjects were the residents of Cimekar Village, Bandung Regency. This research was quantitative associative with primary data and used data collection techniques such as observation, interviews, literature studies, and questionnaires. The sampling technique used was probability sampling. The population of Cimekar Village, consisting of 400 families, served as the sample population, with a sample size of 40 individuals. The results showed a significant effect between risk perception and intention to use (42.2%) for the R2 test, with the t-test result showing t-count > t-table (5.263 > 1.30423). There was a significant effect between financial literacy and intention to use (58.4%) for the R2 test, with the t-test result showing t-count > t-table (7.305 > 1.30423). Simultaneously, there was a significant effect between risk perception and financial literacy on intention to use (71.5%) for the R2 test, with the F-test result showing F-count > F-table (89.037 > 2.45).   Keywords : Financial Literacy; Interest in Using; Risk Perception